High-performance CT features supporting accurate pre-operative tumor staging in colon cancer - Yuan, Jianhua; Jin, Cangzheng; Si, Jianrong; Liu, Baobao; Si, Xiaohan; Chen, Jianzhi (Frontiers in Oncology, 2025)
Background and aimsAccurate pre-treatment tumor staging is essential for treatment decision-making. Multi-slice spiral computed tomography (CT) is currently the standard method for pre-operative clinical tumor staging, but accurately applying the CT findings in tumor staging remains a challenge due to the poor pathological understanding of the CT signs. We aimed to pathologically interpret the key CT findings in order to identify reliable markers for pre-treatment staging of colon cancer.Patients and methodsThe following CT features from 136 colon adenocarcinomas were analyzed: colon wall pliability, outline contour, pericolic fat attenuations and vascularity, tumor fusion with adjacent organs, ascites, tumor size, and relevance between tumor and retroperitoneal fascia. These CT features were corroborated with histopathological findings. The diagnostic performance of these was further analyzed.ResultsBased on the postoperative pathological tumor staging (pT), 136 colon adenocarcinomas were classified into four stages: pT1 (n = 5), pT2 (n = 7), pT3 (n = 96), and pT4 (n = 28). Key findings include the following: (1) soft colon wall is a characteristic of the pT1 tumors, whereas stiff colon wall is a characteristic of the pT2~pT4 tumors; pathologically, stiff colon wall reflects the infiltration of tumor cells with desmoplastic reaction (DR) in muscularis propria; (2) small protuberances may help exclude the pT2 tumors. Histopathologically, small protuberances in pT2 cancer represent the pure DR on the surface of lamina propria, whereas the small protuberances in pT3~pT4 cancers represent the sub-serosal or extra-serosal cancer cell foci enwrapped by DR; (3) the presence of large protuberances, extensive reticulonodular fat stranding, and fusion with surrounding organs and ascites are diagnostic of pT4 tumors; and (4) the presence of extra-fascial nodules/streaks on CT scan could accurately diagnose the ascending/descending colon cancer of pT4 stage. Histologically, the presence of the above five CT features (large protuberances, extensive reticulonodular fat stranding, fusion with surrounding organs, ascites, and extra-fascial nodules/streaks) reflect the farther and deeper infiltration of tumor cells in serosa or retroperitoneal fascia involvement.ConclusionOur studies have identified multiple CT features that are practically useful in identifying and differentiating different stages of colon cancer prior to surgical procedures. These high-performance markers will provide valuable insights to the clinicians in making appropriate decisions in the management of patients with colon cancer.